Magnetic field therapy in patients with cytostatics‐induced polyneuropathy: A prospective randomized placebo‐controlled phase‐III study. Issue 2 (22nd September 2016) - Rick, Oliver; von Hehn, Ulrike; Mikus, Eberhard; Dertinger, Hermann; Geiger, Georg
Abstract : No causal treatment for chemotherapy‐induced peripheral neuropathy (CIPN) is known. Therefore, there is an urgent need to develop a therapy for CIPN. Only scarce clinical data are available concerning magnetic field therapy (MFT) in this context. We conducted a unicentric, randomized, double‐blind, placebo‐controlled phase‐III trial of an MFT device versus placebo. In this study, we randomized 44 patients with CIPN to two treatment groups, where 21 patients were treated with MFT (Group 1) and 23 patients received placebo (Group 2). We evaluated the efficacy of MFT at baseline (T1 ), after 3 weeks of study treatment (T2 ), and after 3 months of study treatment (T3 ). The primary endpoint was nerve conduction velocity (NCV), while secondary endpoints were the Common Toxicity Criteria (CTCAE) score and the Pain Detect End Score at T3 . Seventeen of the patients in Group 1 and 14 patients in Group 2 completed the respective study treatment. The primary endpoint, significant improvement of NCV at T3, was achieved by MFT ( P  = 0.015), particularly for sensory neurotoxicity of the peroneal nerve. Also, in respect to the secondary endpoints, significant improvement ( P  = 0.04) was achieved in terms of the patients' subjectively perceived neurotoxicity (CTCAE score), but not of neuropathic pain ( P  = 0.11). From data in the randomized study presented here, a positive effect on the reduction of neurotoxicity can be assumed for the MFT device. Patients with sensory neurotoxicity in the lower limbs, especially, should therefore be offered this therapy. Bioelectromagnetics. 38:85–94, 2017. © 2016 The Authors. Bioelectromagnetics published by Wiley Periodicals, Inc.